Investigation of cleaning effectivity of waste gases from an incinerator - Sákra, Tomáš; Semerád, Pavel; Ťopek, Miroslav (Univerzita Pardubice, 2000)
Incineration of wastes is supposed to be an effective way of liquidation particularly of those hazardous ones from the medical centers. Most are, therefore, equipped with a modern incinerator. Moreover, flue gases must be effectively cleaned to meet hygienical standards. This works is devoted to the investigation of some parameters characterizing the cleaning section of the Pardubice hospital incinerator. Because the measurement of concentration of some gaseous components in flue gases represents a legal duty of a company, optimization of the acid gases removal (HCl, CL2) and determination of composition of the dust particles was the aim of this first step of the work.
Keywords: ochrana životního prostředí; ovzduší; spalovny; čištění plynů; kyselina chlorovodíková; chlor; polétavý prach